Implementasi Ultrasi Dalam Operasi Penjumlahan Pada Murid Tunarungu Di SLB Negeri Jeneponto - Miskah Rafiqah; Tatiana Meidina; Mustafa Mustafa (JURNAL ORTO DIDAKTIKA, 2023)
This study examines the ability of summation operations in deaf students. The purpose of this study is to find out: 1) The ability of summation operations in grade II deaf students at UPT SLB Negeri 2 Jeneponto during the initial conditions, 2) Improvement of summation operation ability with ultrasy (numeracy snakes) in grade II deaf students at UPT SLB Negeri 2 Jeneponto during intervention, 3) Improvement of summation operation ability with ultrasi (numeracy snakes) in grade II deaf students at UPT SLBN 2 Jeneponto after being given intervention, 4) Improvement of the summation operation ability of grade II deaf students at UPT SLB Negeri 2 Jeneponto after using ultrasy (numeracy snakes and ladders) based on the results of the analysis of initial conditions, conditions when given intervention and conditions after being given intervention. This study used an experimental method with a single subject research (SSR) with an A-B-A design. The results of this study can be concluded: 1) the summation operation ability of AQ subjects before being given treatment is very low based on baseline conditions 1 (A1), 2) the ability of the addition operation of AQ subjects during treatment increases to a high category seen from the analysis under intervention conditions (B), 3) the ability of AQ subjects addition operations after treatment decreases to sufficient categories can be seen from baseline conditions 2 (A2), 4) improvement in the operation ability of summation of AQ subjects based on the results of inter-condition analysis, namely in the conditions before being given treatment, students' ability was very low, increased to the high category during treatment, and from the high category in conditions during treatment decreased to sufficient categories after being given treatment, but the scores obtained by AQ subjects were higher than before being given treatment.